Redox Modification of Cysteine Residues Regulates the Cytokine Activity of High Mobility Group Box-1 (HMGB1) - Yang, Huan (ScholarOne, 2011)
High mobility group box 1 (HMGB1) is a nuclear protein with extracellular inflammatory cytokine activity. It is released passively during cell injury and necrosis, and secreted actively by immune cells. HMGB1 contains three conserved redox-sensitive cysteine residues: C23 and C45 can form an intramolecular disulfide bond, whereas C106 is unpaired and is essential for the interaction with Toll-Like Receptor (TLR) 4. However, a comprehensive characterization of the dynamic redox states of each cysteine residue and of their impacts on innate immune responses is lacking. Using tandem mass spectrometric analysis, we now have established that the C106 thiol and the C23–C45 disulfide bond are required for HMGB1 to induce nuclear NF-κB translocation and tumor necrosis factor (TNF) production in macrophages. Both irreversible oxidation to sulphonates and complete reduction to thiols of these cysteines inhibited TNF production markedly. In a proof of concept murine model of hepatic necrosis induced by acetaminophen, during inflammation, the predominant form of serum HMGB1 is the active one, containing a C106 thiol group and a disulfide bond between C23 and C45, whereas the inactive form of HMGB1, containing terminally oxidized cysteines, accumulates during inflammation resolution and hepatic regeneration. These results reveal critical posttranslational redox mechanisms that control the proinflammatory activity of HMGB1 and its inactivation during pathogenesis.